A 14th century boat from Vordingborg Castle, Denmark, and the use of boats in medieval military operations - Ravn, Morten (Sailing through History. Reading the Past – Imagining the Future: Proceedings of the 16th International Symposium on Boat & Ship Archaeology ISBSA 16, 2024)
In 2012, the remains of a well-preserved 14th century boat were found in the moat at Vordingborg Castle, Denmark. This paper briefly presents the boat-find. Subsequently, the written evidence for the use of small boats comparable to the Vordingborg Boat, in special military operations in Northern Europe – from the Viking-Age to the High Middle Ages – will be discussed. The paper concludes by comparing the Viking-Age and Medieval maritime special military operations with operations conducted in the Second World War (1939–1945).